2016
DOI: 10.11124/jbisrir-2016-002515
|View full text |Cite
|
Sign up to set email alerts
|

The effect of evidence-based, treatment-oriented, clinical practice guidelines on improving patient care outcomes

Abstract: The question that this systematic review aims to address is: does the use of evidence-based, treatment-oriented, clinical practice guidelines by healthcare professionals result in improvements in patient outcomes?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This again ties up with concerns with the lack of human resources and scarcity of expertise among surveyed facilities. Applying guidelines is an intervention to support clinical-decision making and enhance care [ 90 , 91 , 92 , 93 ]. It is however important to include the opinion of key personnel from medical specialties when developing policies and guidelines for prescribing, including antimicrobial prescribing, to enhance guideline acceptability and use [ 37 , 89 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…This again ties up with concerns with the lack of human resources and scarcity of expertise among surveyed facilities. Applying guidelines is an intervention to support clinical-decision making and enhance care [ 90 , 91 , 92 , 93 ]. It is however important to include the opinion of key personnel from medical specialties when developing policies and guidelines for prescribing, including antimicrobial prescribing, to enhance guideline acceptability and use [ 37 , 89 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study point to the use of clinical guidelines as the most important key intervention to enhance RUM (Figure 1). Whilst clinical guidelines have been instrumental in optimizing care and promoting RUM across settings (Ament et al, 2015;Colbeck et al, 2016;Ebben et al, 2018;Brouwers et al, 2019;Niaz et al, 2019;Richards et al, 2019), there are challenges such as regularly updating the guidance or sufficient government or health authority funding for their development and active dissemination in the first place. There can also be concerns with conflicts of interest among guideline developers unless adequately addressed such as the "Wise List" and guidance in Stockholm, Sweden (Gustafsson et al, 2011;Bjorkhem-Bergman et al, 2013;Shnier et al, 2016;DeJong and Steinbrook, 2018;The Lancet, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the wide variety of outcomes measured across individual studies, methodological heterogeneity, and differences in the patient populations being evaluated. 13,14 Clinical practice guidelines can serve as a bridge between the available evidence and its implementation into clinical practice, providing guidance on diagnostic and treatment options on the basis of efficacy, safety, and cost; this in turn increases the likelihood that patients will receive a consistent level of care, regardless of geographic location, clinician type, or medical specialty. 11,15,16 In addition, CPGs that are accompanied by educational tools for patients or caregivers and that are widely disseminated can empower patients to make more informed health care decisions and promote shared decision-making between patients and their providers.…”
Section: Benefits To Patientsmentioning
confidence: 99%
“…Although previous systematic reviews have reported significant improvements, the degree of improvement varies across studies. This may be related to the wide variety of outcomes measured across individual studies, methodological heterogeneity, and differences in the patient populations being evaluated 13,14 …”
Section: Rationale For Clinical Practice Guidelinesmentioning
confidence: 99%